Zimbabwe's CAMPFIRE public investments: impact on education, adaptation and preferences - Matema, Collen (School of Economics, 2021)
The thesis investigates household economic and behavioural implications of public investments funded by communal based wildlife management programmes, such as Communal Areas Management Programme for Indigenous Resources (CAMPFIRE) in Zimbabwe. The thesis focuses on household education and adaptive capacity production. It further investigates determinants of programme stated preferences and behaviour thereof in communal areas of Zimbabwe, using the case of Dande communal area in Mbire district. Since its inception in the late 1980s, there has been debate over the adequacy of the implementation of the CAMPFIRE programme in effecting economic and behavioural change in the respective communities. However, most of the assessments focused on household financial gains, poverty reduction and inequality. Results show that little financial gains accrue to the respective households, with poverty and inequality remaining high. This thesis argues that the main development trajectory in communities implementing communally based wildlife programmes such as CAMPFIRE is biased towards public capital investment; in the form of infrastructure development and respective support for the related services. By design therefore, the programme will have positive impact on access to publicly provided goods and services rather than private goods. By implication, the study further argues that the programme will therefore have varied implications on households' adaptive capacity components that are closely linked to the investment trajectory. Furthermore, there has been mixed feelings regarding the CAMPFIRE programme at the local level, varied to mixed decision outcomes regarding stated preferences on whether to continue the programme or not. The study attempts to decipher this by investigating whether feelings are driven by past wild animal encounters and whether the stated programme preferences are in turn driven by the reported feelings or perceptions of benefit (utility). The study uses posttest data collected through survey-method-choiceexperimental design complemented by qualitative data collection from wildlife producer communities and non-wildlife producing communities in Mbire rural district. I present the exploration on each of the issues in three papers included in the chapters herewith. The first paper investigates effects of the Communal Area Management Programme for Indigenous Resources (CAMPFIRE)'s public investment on education production. The objectives are to estimate the average treatment effect of the programme on children's participation in formal education and identify the socioeconomic inputs that influence education production. The study uses the post-test only control group design and Average Treatment Effect on the Treated (ATET) in estimating the impact of CAMPFIRE programme induced changes on participation in formal education of children of school going-age. I use propensity score estimation to correct for confounding factors, and to allow for comparison of units with similar background characteristics. Results show that education production improves by 12 per cent when children are under the CAMPFIRE programme than when they are not. However, results from education production function show that socio-economic inputs or characteristics are significant factors in explaining variation in education production in CAMPFIRE implementing areas than in nonprogramme implementing areas. This indicates that the programme design is does not remove education disparity between better and less resourced households. Therefore, while public investments for the programme improves education production it needs to be re-configured to address the skewedness. The second paper investigates the average treatment effects on the treated, ATET of community based wildlife management programme on resilience, specifically household adaptive capacity and its different components. The thesis investigates household economic and behavioural implications of public investments funded by communal based wildlife management programmes, such as Communal Areas Management Programme for Indigenous Resources (CAMPFIRE) in Zimbabwe. The thesis focuses on household education and adaptive capacity production. It further investigates determinants of programme stated preferences and behaviour thereof in communal areas of Zimbabwe, using the case of Dande communal area in Mbire district. Since its inception in the late 1980s, there has been debate over the adequacy of the implementation of the CAMPFIRE programme in effecting economic and behavioural change in the respective communities. However, most of the assessments focused on household financial gains, poverty reduction and inequality. Results show that little financial gains accrue to the respective households, with poverty and inequality remaining high. This thesis argues that the main development trajectory in communities implementing communally based wildlife programmes such as CAMPFIRE is biased towards public capital investment; in the form of infrastructure development and respective support for the related services. By design therefore, the programme will have positive impact on access to publicly provided goods and services rather than private goods. By implication, the study further argues that the programme will therefore have varied implications on households' adaptive capacity components that are closely linked to the investment trajectory. Furthermore, there has been mixed feelings regarding the CAMPFIRE programme at the local level, varied to mixed decision outcomes regarding stated preferences on whether to continue the programme or not. The study attempts to decipher this by investigating whether feelings are driven by past wild animal encounters and whether the stated programme preferences are in turn driven by the reported feelings or perceptions of benefit (utility). The study uses posttest data collected through survey-method-choice experimental design complemented by qualitative data collection from wildlife producer communities and non-wildlife producing communities in Mbire rural district. I present the exploration on each of the issues in three papers included in the chapters herewith. The first paper investigates effects of the Communal Area Management Programme for Indigenous Resources (CAMPFIRE)'s public investment on education production. The objectives are to estimate the average treatment effect of the programme on children's participation in formal education and identify the socioeconomic inputs that influence education production. The study uses the post-test only control group design and Average Treatment Effect on the Treated (ATET) in estimating the impact of CAMPFIRE programme induced changes on participation in formal education of children of school going-age. I use propensity score estimation to correct for confounding factors, and to allow for comparison of units with similar background characteristics. Results show that education production improves by 12 per cent when children are under the CAMPFIRE programme than when they are not. However, results from education production function show that socio-economic inputs or characteristics are significant factors in explaining variation in education production in CAMPFIRE implementing areas than in nonprogramme implementing areas. This indicates that the programme design is does not remove education disparity between better and less resourced households. Therefore, while public investments for the programme improves education production it needs to be re-configured to address the skewedness. The second paper investigates the average treatment effects on the treated, ATET of community based wildlife management programme on resilience, specifically household adaptive capacity and its different components. Adaptive capacity denotes the ability of a system to adjust, modify or change its characteristics or actions to moderate potential damage, take advantage of opportunities or cope with the consequences of shocks or stresses. I use Regression Adjustment and Potential Outcome Means (POM) procedures to estimate ATET. Results show that the programme's effect is negative on social, economic and human capacities while positive for transformative or physical capacity. The programme however, has a positive effect on the overall adaptive capacity. The average social capital index for example is 0.011 or 1.1 per cent less when households implement CAMPFIRE programme than the average of 0.061 or 6.1 per cent that would have occurred or obtain if these households were not implementing the programme. The human capital capacity index for programme implementing households is 0.006, less than 0.076, if they were not implementing the programme. The economic capacity index is 0.008 less when treated than the average of 0.068 that would have occurred if the programme-implementing households were not under the programme. However, on physical capacity the potential outcome would be 0.038 higher than 0.183 if the programme-implementing households were not implementing. On the overall household adaptive capacity index, the potential outcome is 0.012 higher than 0.388 that would obtain if the programme-implementing households were not implementing the programme. The results reflect the investment trajectory in the area; a higher proportion of income from the conservation programme has been directed towards public goods provisioning, improving the physical capacity of the respective households. Lessons from the results are that impacts of investments are a result of the investment portfolio configuration. Results of the education production function confirm that the CAMPFIRE programme affects the individual components of adaptive capacity variably; negatively on household social, economic capacities, and positively on household physical capacity, with no significant effect on human capacity and overall household adaptive capacity. Implementing the programme significantly improves access to public service for the poor: with no significant change in economic and social statuses. Furthermore, the results also show that there are other covariates that have significant influence on household capacities, such as having a household member out of the country, or in an urban area, being a widow, belonging to some ethnic groups such as Karanga, and religious affiliation, for example traditional religion. Having a household member in the diaspora for example improves household economic and human capacity, while traditional religion tends to have negative effect on all household adaptive capacities. The key lesson is that the programme is flexible; policy makers can reconfigure it to address critical livelihoods and capacity components as needed. With the active participation of local communities, it can therefore be directed to invest in livelihoods components that are more preferable. In the third paper, I argue that heuristic theory can be used to explain some of the observed or stated human behaviour and stated preferences in communities implementing wildlife based programmes. Heuristics are feelings generated by encounters, painful or pleasurable, which triggers some behaviour traits in the future. The paper aims to determine whether subjects' past encounters with wild animals influence negative affect/feelings; and whether the negative affect leads subjects (1) to engage in self-reported behaviours such as poaching and killing of wild animals and (2) stated preferences towards community based wildlife programmes.